Serum levels of testosterone and SHBG in association with body mass index improve the predictive capability of consolidate tumor biomarkers in pre- and postmenopausal breast cancer patients. (21st February 2018) - Coradini, Danila; Orenti, Annalisa; Venturelli, Elisabetta; Cavalleri, Adalberto; Biganzoli, Elia; Oriana, Saro
Abstract : The study shows that circulating levels of testosterone and sex hormone binding globulin, when associated with body mass index, can improve the predictive capability of consolidate tumor-specific biomarkers in pre- and postmenopausal breast cancer patients. Abstract: Objective: To investigate the contribution of serum levels of testosterone (TS) and sex hormone binding globulin (SHBG) in association with body mass index (BMI) as a surrogate marker of obesity, to the predictive capability of tumor size (T), lymph node (N) and estrogen receptor (ER) status and proliferative activity (TLI). Methods: We investigated 120 women with primary breast cancer and median follow-up of 138 months. Serum levels of TS and SHBG and patient's BMI were evaluated before surgery. The contribution of TS, SHBG, their ratio (TS/SHBG) and BMI to the predictive capability of tumor-specific biomarkers was investigated by Harrell's c statistic. Results: TS alone did not affect prognosis, whereas SHBG was protective in postmenopausal patients, in which BMI was associated with a progressive increase in the relapse-specific hazard ratio (HR). When in combination, TS, SHBG and BMI, affected prognosis in different ways depending on menopausal status. The best predictive capability ( c = 0.78) was observed in postmenopausal patients when at the basic model (N + TLI) were added TS, BMI, TS * BMI interaction, with or without SHBG. In premenopause subgroup, the best predictive capability ( c = 0.67) was provided by the basic model (N + TLI) plus TS and SHBG or their ratio, BMI and TS * BMI or TS/SHBG * BMI interaction. Conclusions: Patient-associated features such as BMI and serum levels of TS and SHBG can improve the predictive capability of consolidate tumor-specific biomarkers in both pre- and postmenopause, thus providing a relevant contribution to the decision-making process.